Argumentative Credibility-based Revision in Multi-Agent Systems - Tamargo, Luciano H. (2012)
We consider the problem of belief revision in a multi-agent system with information stemming from different agents with different degrees of credibility. In this context an agent has to carefully choose which information is to be accepted for revision in order to avoid believing in faulty and untrustworthy information. We propose a revision process combining selective revision, deductive argumentation, and credibility information for the adequate handling of information in this complex scenario. New information is evaluated based on the credibility of the source in combination with all arguments favoring and opposing the new information. The evaluation process determines which part of the new information is to be accepted for revision and thereupon incorporated into the belief base by an appropriate revision operator. We demonstrate the benefits of our approach, investigate formal properties, and show that it outperforms the baseline approach without argumentation.